PUBG Game Addiction, Social Connectedness and Aggression in Young Adults - Kausar, Rukhsana; Rana, Hina; Nouman, Sana; Faisal, Amna (Pakistan Journal of Humanities and Social Sciences, 2024)
In today’s technological era, millions of young adults worldwide engage in violent video s. This study explored how addiction to PUBG game affects aggression, with social connectedness serving as a mediator. Involving 293 PUBG game players (158 men and 135 women) between age of 18 to 25 years (M = 22.21, SD = 1.89), the research used the Gaming Addiction Scale, a revised Social Connectedness Scale, the Buss and Perry Aggression Questionnaire, and a demographic questionnaire. Finding depicts that PUBG game addiction significantly and positively correlates with aggression. However, while the relationship between PUBG game addiction and social connectedness was positive, it was not significant. Social connectedness, on the other hand, was significantly positively related to aggression. Mediation analysis revealed a partial mediation effect of social connectedness on the link between PUBG game addiction and aggression; the indirect path through social connectedness was not significant, though both direct and total effects of addiction on aggression were significant. Independent samples t-tests found significant gender differences in PUBG game addiction, with men scoring higher than women, but no significant differences in social connectedness or aggression. Employment status showed significant differences, with unemployed participants scoring higher in both PUBG game addiction and social connectedness compared to employed participants. However, no significant differences were found in aggression based on employment status, despite unemployed individuals having higher average aggression scores. The findings were compared with existing literature, and recommendations for future research were made, highlighting important implications for young adults’ welfare.